1994
DOI: 10.2307/1941730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonhost Plant on an Insect Herbivore in Diverse Habitats

Abstract: Vegetation texture (i.e., plant density, species diversity, and structural complexity) may influence the abundance of a herbivore by affecting its movement, altering the suitability of host plants, and by changing the herbivore's vulnerability to attack by natural enemies. We investigated these effects on the Mexican bean beetle (Epilachna varivestis) on snap bean (Phaseolus vulgaris) growing in high—and low—density monocultures and intercropped with short (0.5 m) or tall (1.2 m) corn plants (Zea mays). Beetle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 25 publications
3
36
0
2
Order By: Relevance
“…Although this hypothesis predicts that the density of herbivores per host plant increases with increasing plant density, most of the experimental results in the literature contradict this prediction; the number of herbivores per plant is smaller in densely planted fields in most cases (Luginbill and McNeal 1958;Pimentel 1961;Way and Heathcote 1966;A'Brook 1968;Farrell 1976;Solomon 1981;Latheef and Ortiz 1983;Root and Kareiva 1984;Power 1987;Segarra-Carmona and Barbosa 1990; Thompson and Quisenberry 1995). Only a few experiments supported the resource concentration hypothesis (Ralph 1977;Turchin 1988) and several experiments did not detect consistent results (Mayse 1978;Bach 1980;Boiteau 1984;Power 1989;Coll and Bottrell 1994). Therefore, it is valid to adopt the opposite hypothesis, which may be called the 'resource diffusion hypothesis': herbivores use more efficiently hosts that are diffused (i.e., sparsely distributed).…”
Section: Introductionmentioning
confidence: 96%
“…Although this hypothesis predicts that the density of herbivores per host plant increases with increasing plant density, most of the experimental results in the literature contradict this prediction; the number of herbivores per plant is smaller in densely planted fields in most cases (Luginbill and McNeal 1958;Pimentel 1961;Way and Heathcote 1966;A'Brook 1968;Farrell 1976;Solomon 1981;Latheef and Ortiz 1983;Root and Kareiva 1984;Power 1987;Segarra-Carmona and Barbosa 1990; Thompson and Quisenberry 1995). Only a few experiments supported the resource concentration hypothesis (Ralph 1977;Turchin 1988) and several experiments did not detect consistent results (Mayse 1978;Bach 1980;Boiteau 1984;Power 1989;Coll and Bottrell 1994). Therefore, it is valid to adopt the opposite hypothesis, which may be called the 'resource diffusion hypothesis': herbivores use more efficiently hosts that are diffused (i.e., sparsely distributed).…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, insect pest damage tends to be lower in diverse agroecosystems (Andow 1986;Coll and Bottrell 1994). Root (1973) has proposed two hypotheses to explain lower pest problems in diverse agroecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…what densities these organisms can reach in monocultures and polycultures. Studies in agro-ecosystems have indicated that populations of herbivorous insects generally reach higher levels in simple systems than in diverse ones (Pimentel 1961;Coll and Bottrell 1994). Root (1973) proposed two explanations for this pattern, which are not mutually exclusive: (1) the enemies hypothesis, which states that predators and parasites are more effective in diverse systems than in simple ones; and (2) the resource concentration hypothesis, according to which specialist herbivores more easily find, stay in, and reproduce in simple systems of their host plants.…”
Section: Introductionmentioning
confidence: 99%